The Influence of Consumers’ Purchase Intention Factors on Willingness to Pay for Renewable Energy; Mediating Effect of Attitude - Nazir, Mehrab; Tian, Jian (Frontiers in Energy Research, 2022)
This research was conducted to examine the influences of renewable energy and its marketing factors (social media exposure, relative advantage, awareness, ease of use, and cost) on purchase intention. It analyzed seven concepts: social media exposure, relative advantage, awareness, ease of use, cost, attitude, and purchase intention and deliberated their relationships. The conceptual framework is based on the theory of planned behavior and the unified theory of acceptance. Structural equation modelling technique used to test the statistical relationship between proposed hypotheses with a sample size of 497 shoppers. The main findings revealed interesting consumer purchase intention regarding renewable energy technology. The results showed a significant positive relationship between influential determinants (social media exposure, relative advantage, ease of use, awareness, and cost) and purchase intention towards the use of renewable energy technology. This study suggests that these marketing approaches can be used as a brand marketing strategy to enhance customer purchase intention. The study's findings will help in making decision in the renewable energy sub-sector. Furthermore, the findings of this study could be used as a reference by the government when making decisions about renewable energy deployment. Keywords: Social media, Relative advantage, Ease of use, Awareness, Cost, Attitude, and Purchase intention